Human perceptuality-aware tone-mapping-based dynamic voltage scaling for an amoled display smartphone - Suh, Simon; Hong, Seok Min; Kim, Young Jin; Park, Jong Sung (Electronics (Switzerland), 2021)
In recent years, people have wanted to watch high dynamic range imagery which can give high human visual satisfaction on smartphones and demand longer smartphone battery time. However, compression of dynamic range using tone-mapping operators is required in smartphones because most smartphone displays currently have a low dynamic range, and this causes loss of local contrast and details to compress dynamic range. Thus, in this paper we propose a novel dynamic voltage scaling scheme tightly coupled with a modified tone-mapping operator to achieve high power saving as well as good human perceptuality on an AMOLED display smartphone. In order to perform a human perceptuality-aware voltage control, we control display panel voltage to save power consumption and use a well-adjusted global tone-mapping operator to convert image brightness and unsharp masking to enhance local contrast and details and control. We implement the proposed scheme on the AMOLED display Android smartphone and experiment with various high dynamic range image databases. Experimental results show that not only tone-mapped images but also general images are improved in terms of human visual satisfaction and power saving, compared to conventional techniques.
Keywords: AMOLED display; Dynamic voltage scaling; High dynamic range; Human perceptuality; Smartphones; Tone mapping